The European Union : how does it work? - Bomberg, Elizabeth E.; Peterson, John, 1958-; Corbett, Richard, 1955- (New European Union series., 2012)
An introduction to the European Union's structure and operations for those coming to the subject for the first time. Leading scholars and practitioners cut through the complexity to explain how the EU really works and why it matters.